Dual resonance circular ring-shaped metamaterial absorber with wide operating angle - Ayop, O. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper proposed a dual resonant circular ring-shaped metamaterial absorber (MMAbs) with wide operating angle in X-band frequency. The structure is constructed on FR4 substrate. The resonating elements are designed using two circular rings structure with different radius. The resonating elements are printed on the top surface of FR4 substrate, while at the bottom layer; a full copper layer is placed. The performance of the designed structure is observed using CST software. From the simulation, the proposed structure achieves high absorbance, which is 93.80% and 86.19% at 9 GHz and 11 GHz respectively for normal incident EM wave. Then, the structure is also simulated for oblique incident angles. It is observed that the operating angle of the proposed metamaterial absorber is 69° for both TE and TM polarization. The measurement is done to validate the simulated result.